Development of Travel Time Models for Split-Platform Automated Storage and Retrieval System Under Varying Dwell Point Policies - Vasili, Mohammadreza (2007)
One important operational aspect of the SP-AS/RS, which contributes to the system response time, is the dwell point policy of the platforms. There are several dwell point policies for SP-AS/RS and an effective dwell point policy may reduce the response times of this system. The travel time analysis for SP-AS/RS has not been adequately investigated in previous research and only one reliable travel time model can be found in literature, which is under stay dwell point policy. But it is not logical to select this travel time model as the base, without any analysis of travel time models under other dwell point policies. In this research, two continuous travel time models are developed for SP-AS/RS under return to middle and return to start dwell point policies. In the previous design of SP-AS/RS, hand-over stations and input/output (I/O) station are located at the same end of the rack. In this study a new configuration alternative for SP-AS/RS is introduced by shifting the position of hand-over stations and I/O station to the middle of the rack. Using this configuration, the average handling time for a range of shapes can be greatly reduced. A continuous travel time model is also developed for this new configuration. To evaluate all continuous models for their accuracy, the models are validated by using the computer simulations. A user interface computer program is developed to computerize the calculation of travel times under varying dwell point policies and find the best policy, for different configurations. Comparing the results of new models which were developed in this thesis with previous ones, showed that for the shapes of the racks that have shape factors (b) more than 2 (b > 2), stay dwell point policy is more preferable. While, for the shapes that have shape factors less than or equal to 2 (b £ 2), a new configuration of SP-AS/RS gives the better results in the case of average operation time. The most preferable shapes for AS/RS are those that their shape factors are less than or equal to 2 (b £ 2). Therefore in many cases the new configuration performs better than previous design under varying dwell point policies, but generally the optimal rack design will largely depends on the characteristics of different applications.